Multiplicative Dirac system - Gulsen, Tuba; Yilmaz, Emrah; Goktas, Sertac (Elsevier, 2022)
We define a Dirac system in multiplicative calculus by some algebraic s t ructures. Asymptotic estimates for eigenfunctions of the multiplicative Dirac system are obtained. Eventually, some fundamental properties of the multiplicative Dirac system are examined in detail.
Keywords: Dirac system; multiplicative calculus; Eigenvalue; Eigenfunction; simplicity